2021
DOI: 10.3390/nu13113908
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Nutrient Intake of Han and Dongxiang Smallholder Farmers in Poverty Areas of Northwest China

Abstract: This study aimed to evaluate the status of dietary diversity and nutrient intake among Han and Dongxiang smallholder farmers in poor rural areas of northwest China. In this cross-sectional study, dietary intake was assessed in 499 smallholder farmers aged 18–75 years from two nationally designated impoverished counties in Gansu Province, China, using three consecutive 24 h dietary recalls. The dietary diversity score (DDS) and nutrient adequacy ratio (NAR) were adopted to assess dietary diversity and micronutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Using concatenated shared single copy genes, we obtained a well-resolved phylogenetic tree. In this study, strains from northwest China were largely clustered, while those from other regions were scattered among a variety of clusters, which is conjectured to be due to the unique dietary habits that exhibited high consumption of grain food, while consumption of vegetables, fruits, and fish was inadequate in northwest China [ 27 ]. However, given the small sample size, substantiating this speculation would require a further survey of dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…Using concatenated shared single copy genes, we obtained a well-resolved phylogenetic tree. In this study, strains from northwest China were largely clustered, while those from other regions were scattered among a variety of clusters, which is conjectured to be due to the unique dietary habits that exhibited high consumption of grain food, while consumption of vegetables, fruits, and fish was inadequate in northwest China [ 27 ]. However, given the small sample size, substantiating this speculation would require a further survey of dietary habits.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic brands made considerable effort to highlight the abundance of minerals in their products, which appeared to be overlooked by international brands and might be explained by more in-depth local knowledge of the market segment’s unmet needs. Prior research, for instance, has continuously documented a significant deficiency of minerals amongst Chinese people [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…and fever symptoms in the past three months. (3) No infectious diseases (AIDS, hepatitis B, syphilis, etc.). (4) No history of intake of antibiotics, antiviral, antifungal, or analgesic drugs in the past three months.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Many studies have shown that dietary diversity has beneficial effects on nutritional status at different ages, especially in children (3,(17)(18)(19). For instance, dietary diversity has been proven to be related to micronutrient adequacy in multiple age groups in both developing and developed countries (1,2,(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%